Rowing: the influence of the angle of inclination of the leg support on the force in the paddle - Budescu, E.; Merticaru, E.; Chirazi, M. (IOP Conf. Series: Materials Science and Engineering, Volume 444, Theory of Mechanisms and Machinery. Robotics, 2018)
This study is aiming to emphasize the relation between the force at the paddle and the inclination angle of the support of the leg on the skiff, depending on the anthropometric dimensions of the sportsman. This angle, which is adjustable, makes the reaction force between the support and the leg to be decomposed into two components, namely: a horizontal component equivalent to the force at the paddle and a component along the support which is determining the sliding force between the leg and the support. The reaction force between the leg and the support depends also, on the anthropometric dimensions of the thigh and the shank as well as on the extension angles of the thigh and shank. The whole assembly formed of shank, thigh and the sliding chair on which the sportsman is sitting can be likened to an eccentric crank-piston mechanism. The numerical study emphasized that the increasing angle of inclination of the support produces the increasing of the horizontal component of the reaction force leg-support. On the other side, when the shank and the thigh are in prolongation, the inclination angle of the support has to be around 75 degrees so that the entire sole of the foot to be in contact with the support. Using the relations emphasized in the paper, there can be determined the optimum angle, personalized, for each sportsman.